Przemiany obrazu ziemiaństwa w powojennej polskiej historiografii - Łuczak, Agnieszka (Instytut Pamięci Narodowej, 2011)
Celem niniejszego artykułu jest zaprezentowanie przemian obrazu polskiego ziemiaństwa w polskiej historiografii po 1944 r. Podejmując to zagadnienie, trzeba pamiętać, że problem oceny ziemiaństwa oraz jego roli społecznej, kulturowej i gospodarczej był w omawianym okresie uwikłany w kontekst polityczny. Rozważania historyków w kwestii ziemiaństwa były pełne rozmaitych, często sprzecznych opinii, a przewartościowania w ocenach miały ścisły związek z przełomami politycznymi lat 1944 oraz 1989. W artykule zostaną zaprezentowane opinie historyków, publicystów, a także przykłady propagandy i retoryki politycznej, tworzące często całkowicie różne obrazy polskiego ziemiaństwa. W artykule zastanawiam się, czy mimo tak odmiennych stanowisk doszło do dyskusji między historykami, zwłaszcza po 1989 r., kiedy po zniesieniu cenzury pojawiła się możliwość swobodnej wymiany myśli. Czy został przez naukowców wypracowany jakiś obszar konsensusu w interesującej nas kwestii?

The image of the Polish landed gentry presented by historians after the year 1945 was subject to changes and gradually evolved which was a consequence of political pressure on the researchers dealing with recent history. Both the notion of the landed gentry and the evaluation of the role which this group played in the life of Polish society during the period of partitions of the II Republic of Poland were subjected to revaluation. The most characteristic views of the historians on the Polish landed gentry have been presented in the article. The author presents various definitions of the landed gentry, starting from the ones which presented it as a parasitic class, constituting part of the capitalist class, whose main source of income was the exploitation of farm-laborers, and ending with the contemporary definition emphasizing the social-cultural functions of this group which had particular features, mainly of noble and national origin, specific mentality, social, political and national awareness, lifestyle and system of values. The views of the historians concerning the role of the landed gentry (from the political one to the cultural one) have been discussed in the article. Most of the attention was devoted to the economic role of the landed gentry, particularly through the perspective of the agricultural reform conducted in the years 1944–1948. The landed gentry was often described in historiography as the elite, enjoying the prestige of the whole society, however, the historians tried to explain the causes of this phenomenon in different, often dissimilar ways.
Keywords: ziemiaństwo; historiografia PRL; obraz historiograficzny; ideologizacja historii